Evaluasi Penggunaan Rekam Medis Elektronik (RME) dalam Peningkatan Keamanan Data Pasien di Puskesmas Haurwangi Kabupaten Cianjur - Yayan Ari Kurniawan; Andriani, Rian; Widjaja, Yani Restiani (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Digital transformation in the health sector has driven the adoption of Electronic Medical Records (EMR) as an innovative solution to replace manual record-keeping systems traditionally used by healthcare providers. The implementation of EMR in primary healthcare centers plays a strategic role, as it has the potential to improve service efficiency, enhance the quality of patient care, and support data integration across service units. Nevertheless, the adoption of EMR also presents new challenges, particularly related to patient data security and protection. This study aims to evaluate the use of Electronic Medical Records in enhancing patient data security at Haurwangi Public Health Center. The research employed a case study design with a descriptive qualitative approach. Data were collected through observation and in-depth interviews using the GAP Analysis: Status of ISO 27001 Implementation – Checklist instrument. The results indicate that the use of EMR at Haurwangi Public Health Center has supported data integration from patient registration to referral processes and facilitated the preparation of both internal and external reports. However, based on the GAP Analysis referring to the ISO 27001:2022 standard, patient data security requirements have not been fully met, resulting in potential risks of data breaches. Therefore, it is necessary to revise strategic policies in line with current regulations, enhance human resource competencies, implement comprehensive risk management, and conduct regular internal and external audits to strengthen information security based on the principles of Confidentiality, Integrity, and Availability (CIA Triad).